1992
DOI: 10.1136/emj.9.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Should nurses be allowed to request X-rays in an accident & emergency department?

Abstract: SUMMARYA prospective study was carried out during the month of November, 1990 in the A&E Department, St John's Hospital, Livingston in order to assess the extended role of the A&E nurse and their ability to request X-rays prior to patients being seen by a doctor.A total of 579 randomly selected patients were triaged by A&E Department nurses. Almost 3/4 of these patients were X-rayed at the request of the triage nurse. Less than 7% of these X-rays were considered to have been unnecessary by the doctor who subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 0 publications
1
19
1
1
Order By: Relevance
“…Fifty eight nurse practitioners, forty three experienced senior house officers, and 41 inexperienced senior house officers were tested, and the mean scores are set out in table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty eight nurse practitioners, forty three experienced senior house officers, and 41 inexperienced senior house officers were tested, and the mean scores are set out in table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The results of Kelly, McCarthy, Richardson, Parris, and Kerr (1995) suggested that the average timesavings for the patient could be in the order of 45 min. Others studies found that the timesavings for patients ranged from 8 to 60 min when nurses initiated radiographs at the point of triage (Davies, 1994, Macleod & Freeland 1992Parris et al, 1997). Furthermore, in a recent study, a decrease of 45 min in the overall waiting time was noted for patients with limb injuries when nurses utilized protocols (Sorensen et al, 2012).…”
Section: Wait Times: Patient and Staff Satisfactionmentioning
confidence: 95%
“…According to Davis (1994), implementing nurse-initiated radiographs at the triage stage can reduce delays in patient assessment and management. Several studies (Ching, Leng, & See, 1999;Lee et al, 1996;Macleod & Freeland, 1992;Stiell et al, 1993;Ward, 1999;Wilkinson, 1999) support this claim.…”
Section: Wait Times: Patient and Staff Satisfactionmentioning
confidence: 97%
“…Another difficulty with nurse triage is the limitations that may be placed on a nurse's practice. It has been shown that nurses can adhere to X-ray protocols as well as an A&E officer (Macleod & Freeland, 1992) and steer patients successfully to their GP (Carew- McColl & Buckles, 1990). The overall impact on a department may still be limited.…”
Section: Introductionmentioning
confidence: 99%